Internship Preparation and Social Work: Mental and Emotional in Its Implementation - Henrique Cesário da Costa (International Journal Labs, 2026)
Internship constitutes a critical component of higher education, particularly in Social Work, as it bridges theoretical knowledge and field-based professional practice. In the context of Timor-Leste, internship implementation often occurs in remote areas characterized by geographical limitations, strong socio-cultural traditions, and complex community dynamics. This study aims to analyze the mental and emotional preparation of Social Work students during their internship experiences and to examine the socio-cultural factors influencing their adaptation process. Using a qualitative descriptive approach, this research applies documentary analysis and content analysis of official internship reports and relevant literature. The findings indicate that students initially experience anxiety, social isolation, and psychological pressure due to environmental changes, cultural differences, and separation from family. However, through adaptive communication, cultural sensitivity, and reflective practice, students gradually develop emotional resilience, professional maturity, and socio-cultural competence. The study highlights that mental and emotional preparedness is a fundamental determinant of internship success. Without adequate preparation, students risk stress and disengagement; conversely, structured socio-emotional preparation enhances professional identity formation and community integration. The study recommends integrating socio-emotional training, intercultural competence, and psychological mentoring into the Social Work curriculum to strengthen students’ readiness for field practice.